2013
DOI: 10.1109/tvcg.2012.315
|View full text |Cite
|
Sign up to set email alerts
|

Perceptually Driven Visibility Optimization for Categorical Data Visualization

Abstract: Visualization techniques often use color to present categorical differences to a user. When selecting a color palette, the perceptual qualities of color need careful consideration. Large coherent groups visually suppress smaller groups and are often visually dominant in images. This paper introduces the concept of class visibility used to quantitatively measure the utility of a color palette to present coherent categorical structure to the user. We present a color optimization algorithm based on our class visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 28 publications
0
33
0
3
Order By: Relevance
“…Their work is based on CIE L*a*b* space, for which the authors pointed out its limitation, suggested a remedy of using CIE1994 and CIEDE2000, and reasoned about the algorithmic difficulty in using CIEDE2000. Our work differs from [29] in several ways: (i) We focused on the optimization of a color palette rather an individual visualization; (ii) We enabled users to define constraints in a more meaningful way and demonstrated the use of such constraints through a real-world application; (iii) We made use of CIEDE2000, studied a number of optimization algorithms and identified their relative merits in addressing the algorithmic difficulty; and (iv) We provided a web application to make this technique available to a wider range of users.…”
Section: Related Workmentioning
confidence: 68%
See 4 more Smart Citations
“…Their work is based on CIE L*a*b* space, for which the authors pointed out its limitation, suggested a remedy of using CIE1994 and CIEDE2000, and reasoned about the algorithmic difficulty in using CIEDE2000. Our work differs from [29] in several ways: (i) We focused on the optimization of a color palette rather an individual visualization; (ii) We enabled users to define constraints in a more meaningful way and demonstrated the use of such constraints through a real-world application; (iii) We made use of CIEDE2000, studied a number of optimization algorithms and identified their relative merits in addressing the algorithmic difficulty; and (iv) We provided a web application to make this technique available to a wider range of users.…”
Section: Related Workmentioning
confidence: 68%
“…Lee et al [29] presented a color optimization algorithm that maximizes the perceptual distances among a set of categorical colors. Their work is based on CIE L*a*b* space, for which the authors pointed out its limitation, suggested a remedy of using CIE1994 and CIEDE2000, and reasoned about the algorithmic difficulty in using CIEDE2000.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations